The Rainmaker - Coppola, Francis Ford, 1939-; Damon, Matt.; Danes, Claire, 1979-; Voight, Jon, 1938-; Grisham, John.; Constellation Films; American Zoetrope (Firm) (Hollywood, CA : New York : Paramount, Island Books, 1995)
A rookie lawyer in over his head on a high-profile case hires a feisty paralawyer who specializes in flunking the bar. Their chances of winning are slim to none until they uncover a trail of corruption.
Originally released as a motion picture.
Based on the novel by John Grisham.
Matt Damon, Claire Danes, Jon Voight, Mary Kay Place, Mickey Rourke, Danny DeVito.
Rated PG-13.
DVD.
Closed captioned for the hearing impaired.
Keywords: Leukemia -- Patients -- Fiction; Compañías de seguros -- Prácticas ilegales -- Teatro; Abogados -- Teatro; Memphis (Tenn.) -- Drama; Feature films; Video recordings for the hearing impaired